SYNTHESIS AND CHARACTERIZATION OF NOVEL GIOMERS FOR DENTAL APPLICATIONS - HODISAN, Ioana; PREJMEREAN, Cristina; PETEAN, Ioan; PRODAN, Doina; BURUIANA, Tinca; COLCERIU, Loredana Elena; BARBU-TUDORAN, Lucian; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The aim of the present work was to prepare and characterize a series of dental giomers and their corresponding dental adhesive and to evaluate the adhesion of the new materials at the restoration/tooth interface. The experimental giomers were prepared as monopastes by blending the resin matrices, a new pre-reacted glass, a radiopaque glass and fluorhydroxyapatite. The novelty of the work is represented by the using of a polyalkenoic acid based on acrylic acid, itaconic acid and N-acryloyl –L-leucine as the main component of the pre-reacted glass and of the primer in the adhesive system. In addition, the using of an original synthesized urethane tetra-methacrylate Bis-GMA analogue (Bis-GMAexp) as base monomer in the resin represents another element of novelty. The morphology of giomer samples was investigated by scanning electron microscopy. The sealing ability was tested by dye penetration method completed with atomic force microscopy investigation. The microleakage was evaluated using the score method. The results pointed out a remarkable dentin sealing for the new adhesive system and a strong adhesion at Bis-GMAexp-based giomer/ adhesive system/tooth interfaces in substantial agreement with very low value of microleakage.